2021
DOI: 10.1101/2021.05.17.444449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Campylobacter in air samples from poultry houses using shot-gun metagenomics – a pilot study

Abstract: Background: Foodborne pathogens such as Campylobacter jejuni are responsible for a large fraction of the gastrointestinal infections worldwide associated with poultry meat. Campylobacter spp. can be found in the chicken fecal microbiome and can contaminate poultry meat during the slaughter process. The current standard methods to detect these pathogens at poultry farms use fecal dropping or boot swaps in combination with cultivation / PCR. In this study, we have used air filters in combination with shotgun met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Using receiver operating characteristic (ROC) curves, they found that the accuracy of organism detection was maximized when this ratio was 10. A study on Campylobacter in air of poultry houses used a threshold of 50 reads per sample based on the number of putative false Campylobacter reads in mock samples ( Haverkamp et al., 2021 ), whereas a study on Klebsiella in human faecal samples suggested an abundance threshold of 0.01% to accurately estimate its occurrence based on spiked microbiomes ( Lindstedt et al., 2022 ). We choose to use unique k -mer counts as parameter for metagenomic abundance threshold in place of read counts as the former have improved species-recall and better separation between negative and positive samples ( Breitwieser et al., 2018 ), increasing the robustness of the metagenomic assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using receiver operating characteristic (ROC) curves, they found that the accuracy of organism detection was maximized when this ratio was 10. A study on Campylobacter in air of poultry houses used a threshold of 50 reads per sample based on the number of putative false Campylobacter reads in mock samples ( Haverkamp et al., 2021 ), whereas a study on Klebsiella in human faecal samples suggested an abundance threshold of 0.01% to accurately estimate its occurrence based on spiked microbiomes ( Lindstedt et al., 2022 ). We choose to use unique k -mer counts as parameter for metagenomic abundance threshold in place of read counts as the former have improved species-recall and better separation between negative and positive samples ( Breitwieser et al., 2018 ), increasing the robustness of the metagenomic assay.…”
Section: Discussionmentioning
confidence: 99%
“…These factors will vary between pathogenic targets as well as matrix under investigation. Further, misclassifications of sequences are commonly encountered, especially when using deep sequencing, as shown in several studies where metagenomic classifiers readily identify hundreds of species in known mock communities despite only a few being present ( Haverkamp et al., 2021 ). Additional sources of misclassifications include contamination, presence of kitome, index hopping and sample bleeding ( Mitra et al., 2015 ; van der Valk et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%